Studi Kasus Balita Usia 14 Bulan dengan Gizi Buruk Tanpa Komplikasi di Desa Blang dalam Geunteng Puskesmas Nisam Tahun 2026 - Salsa Nabila Inong Ranadhana; Wirdatul Ulfia; Muhammad Rizky Simanjutak; Maulida Sari; Noviana Zara (Pusat Riset dan Inovasi Nasional, 2026)
Malnutrition and stunting among children under five remain major public health challenges in developing countries, including Indonesia. These conditions are associated with increased morbidity, mortality, impaired cognitive development, and reduced productivity in adulthood. Stunting reflects chronic nutritional deficiencies, while severe malnutrition indicates acute or prolonged inadequate nutrient intake, often exacerbated by infections, poor caregiving practices, and unfavorable socioeconomic conditions. This case report aims to describe the clinical condition, contributing factors, management, and outcomes of a 14-month-old female toddler diagnosed with severe malnutrition and stunting without complications in Blang Dalam Geuteung Village, Nisam Subdistrict, North Aceh Regency. The assessment was conducted using a family medicine approach, incorporating detailed history taking, physical examination, anthropometric measurements, and nutritional status evaluation based on World Health Organization Z-score indicators. Interventions included nutritional rehabilitation through appropriate dietary intake, family education on balanced nutrition and proper feeding practices, routine growth monitoring, and optimization of primary healthcare services. The results showed gradual improvement in the child’s nutritional status, evidenced by weight gain, better appetite, and improved feeding patterns following the intervention. This case highlights the importance of early detection, comprehensive family-centered management, and continuous monitoring in addressing malnutrition and stunting at the primary care level. Strengthening community-based interventions, improving caregiver knowledge, and enhancing collaboration between healthcare providers and families are essential to reduce the burden of malnutrition and support optimal child growth and development.